2002
DOI: 10.1016/s0925-4773(02)00391-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the Tab1 gene causes embryonic lethality and defects in cardiovascular and lung morphogenesis

Abstract: The transforming growth factor-beta (TGF-beta) superfamily consists of a group of secreted signaling molecules that perform important roles in the regulation of cell growth and differentiation. TGF-beta activated kinase-1 binding protein-1 (TAB1) was identified as a molecule that activates TGF-beta activated kinase-1 (TAK1). Recent studies have revealed that the TAB1-TAK1 interaction plays an important role in signal transduction in vitro, but little is known about the role of these molecules in vivo. To inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 60 publications
1
68
0
Order By: Relevance
“…After E10.5, the embryonic structures were resorbed in the Tak1 mutants. Interestingly, the mutant phenotype of Tak1 embryos is substantially different from Tab1 (abnormal cardiovascular and pulmonary morphogenesis) and Tab2 (liver degeneration and apoptosis) mutant embryos (Table 2; Komatsu et al 2002;Sanjo et al 2003). The phenotypes of the mutant embryos suggest that the TAK1 complex does not only function as a single unit but, instead, that each component has a distinct role during development.…”
Section: Abnormal Development Of Neural Tube In Tak1 Mutant Embryosmentioning
confidence: 92%
See 1 more Smart Citation
“…After E10.5, the embryonic structures were resorbed in the Tak1 mutants. Interestingly, the mutant phenotype of Tak1 embryos is substantially different from Tab1 (abnormal cardiovascular and pulmonary morphogenesis) and Tab2 (liver degeneration and apoptosis) mutant embryos (Table 2; Komatsu et al 2002;Sanjo et al 2003). The phenotypes of the mutant embryos suggest that the TAK1 complex does not only function as a single unit but, instead, that each component has a distinct role during development.…”
Section: Abnormal Development Of Neural Tube In Tak1 Mutant Embryosmentioning
confidence: 92%
“…However, the physiological roles of mammalian TAK1, TAB1, and TAB2 in inflammatory signaling in vivo remain to be definitively established. TAB1-deficient mouse embryonic fibroblasts (MEFs) have been generated; however, TAB1 function has not been tested in TNFR1 and IL-1R/TLRmediated signaling (Komatsu et al 2002). Surprisingly, TAB2-deficient MEFs are capable of activating IKK and JNK normally in response to TNF-␣ or IL-1 (Sanjo et al 2003).…”
mentioning
confidence: 99%
“…These results reinforce earlier experiments showing that RNAi and chemical inhibitors of TAK1 blocked IKK and JNK activation by multiple pathways . In contrast to TAK1, deletion of TAB1 or TAB2 did not affect NF-kB activation by IL-1b or TNFa (Komatsu et al, 2002;Sanjo et al, 2003). As biochemical experiments had shown that TAB1 is dispensable for IKK activation by TRAF6 in vitro (Wang et al, 2001), it is likely that TAB1 is involved in other signalling pathways (e.g., TGF-b) instead of the NFkB pathway.…”
Section: The Traf Family Of Ubiquitin-protein Ligases (E3)mentioning
confidence: 94%
“…Further studies are required to determine the physiological context of TAB1-mediated p38 MAPK activation. Importantly, the recent description of Tab1 −/− mice, which die during early embryogenesis with cardiovascular and lung dysmorphogenesis, will facilitate this analysis (Komatsu et al 2002).…”
Section: Activation Of P38 Map Kinase By Mapkk-independent Mechanismsmentioning
confidence: 99%